(untitled) (World Bulletin of Management and Law, 2022)
The research dealt with soft leadership skills as an independent variable and strategic pitfalls as a dependent variable. A sample of managers working in first-class hotels in Baghdad was selected. The research relied on the opinions of 30 managers. The research problem was diagnosed through field experiments conducted by researchers in first-class hotels in Baghdad. It was suggested that the dimensions of soft leadership skills contribute to addressing weak strategic pitfalls. The research sought to achieve a set of goals, the most important of which are: Describe the dimensions of the research variables and test the correlation and impact relationship between the research variables in the first-class hotels in Baghdad. To achieve these goals, the research relied on the analytical descriptive approach, and the researcher used the questionnaire in the practical aspect of the research, as well as the research and studies related to the subject of the research in the theoretical aspect with reliance on (SPSS) to test and analyze the hypotheses of the relationship and the effect between the research variables. The research concluded with a set of recommendations